An Analysis of Students’ Science Process Skills in Learning Chemical Bonding - Tri Luthfi Okta Fianaumi (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
This study analyzes students’ science process skills in the topic of chemical bonding, aiming to assess the extent of their mastery in various skill aspects in Grade XI at SMA Negeri 1 Indralaya Utara. The research employed a quantitative approach with a descriptive design. The subjects were Grade XI students in the 2024/2025 academic year who were studying chemical bonding, while the object of the research was science process skills observation sheets. The results revealed that students demonstrated a very high level of science process skills across six measured indicators. The percentage of achievement in each aspect was as follows: observing skills (87%), making inferences or drawing conclusions (85%), predicting (89%), and communicating (89%). In addition, classifying skills reached 91%, and experimenting skills scored 86%, both of which were also categorized as very good. Overall, the average mastery of students' science process skills was 87%, indicating excellent performance. These findings suggest that students are capable of carrying out scientific activities such as observing, classifying, inferring, and effectively communicating experimental results, while also demonstrating an understanding of the relationships between variables during practicum activities.